Handbook of research on cloud computing and big data applications in IoT - Gupta, B. B., 1982- (Engineering Science Reference, , an imprint of IGI Global, 2019)
"This book examines the latest research results on cloud computing and explores the broad applicability and scope of these trends on an international scale, venturing into the hot-button issue of IT services evolution and what we need to do to be prepared for future developments in cloud computing. It also explores big data applications in IoT"--